2013
DOI: 10.1016/j.msec.2013.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite induces spontaneous polymerization of model self-etch dental adhesives

Abstract: The objective of this study is to report for the first time the spontaneous polymerization phenomenon of self-etch dental adhesives induced by hydroxylapatite (HAp). Model self-etch adhesives were prepared by using a monomer mixture of bis[2-(methacryloyloxy)ethyl] phosphate (2MP) with 2-hydroxyethyl methacrylate (HEMA). The initiator system consisted of camphorquinone (CQ, 0.022 mmol/g) and ethyl 4-dimethylaminobenzoate (4E, 0.022–0.088 mmol/g). HAp (2–8 wt.%) was added to the neat model adhesive. In a dark e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The laboratory and in vitro studies have been investigated in detail and are tabulated in Table 2. 2. HA A total 30 studies 20, was found to be based on the incorporation of HA in dental resin matrices, where microparticles 20,[63][64][65][66][67][68][69][70][71][72] , nano-particles/rods/fibers 71,[77][78][79][80][81][82][83][84][85][86][87]89,90) and whiskers/fibrous [73][74][75][76][77][78][79][80] HA have been mainly used. A study showed the doping of silver in HA and investigated the in vitro bond strength 88) .…”
Section: Acpmentioning
confidence: 99%
“…The laboratory and in vitro studies have been investigated in detail and are tabulated in Table 2. 2. HA A total 30 studies 20, was found to be based on the incorporation of HA in dental resin matrices, where microparticles 20,[63][64][65][66][67][68][69][70][71][72] , nano-particles/rods/fibers 71,[77][78][79][80][81][82][83][84][85][86][87]89,90) and whiskers/fibrous [73][74][75][76][77][78][79][80] HA have been mainly used. A study showed the doping of silver in HA and investigated the in vitro bond strength 88) .…”
Section: Acpmentioning
confidence: 99%
“…Sufficiently flexible resin layer could resist the polymerization shrinkage stress of the restorative composite (35), thus maintaining the bonding performance. Moreover, Young's modulus seems to be dependent of hydroxyapatite content, which presence may induce spontaneous polymerization of self-etch adhesive systems (36). Nanoindentation and bond-strength testing Figure 1.…”
Section: Characteristics and Propertiesmentioning
confidence: 99%
“…It is believed that the initiation mechanism is associated with the tertiary amine (4E) and acid (acidic monomer) complex, mediated by a base trigger (HAp). 21,22 Radical polymerization initiated by amine-acid complex has been reported previously [28,29] in dental bonding research. However, in these studies, the amines used are carboxyl-containing amines (e.g., N-phenylglycine, N-phenyliminodiacetic acid), which contain amine and acid on the same molecule.…”
Section: Discussionmentioning
confidence: 81%
“…The superior performance of 10-MDP has made it one of the most popular monomers in self-etch adhesives. According to previous studies, 21,22 the interaction between acidic monomer 2MP and tertiary amine 4E, concentration of both 4E and HAp, and the acidity of the selfetch adhesive played critical roles in the occurrence of this kind of self-cure. Thus, it is totally unknown if self-cure of other acidic monomers, especially those used in commercial self-etch adhesives, would happen using this 4E-HAp system.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation